Investigating the neural substrates of Chinese character processing - Wu, Chiao-Yi (2014)
Most of the existing models of language have been based on alphabetic languages; however, growing evidence has shown that character language processing, such as Chinese, might recruit differentiated brain networks due to its unique linguistic features. This thesis proposed a research framework by using functional magnetic resonance imaging (fMRI) to investigate the neural mechanisms underlying Chinese character processing. We hoped to further explore whether Chinese character processing involved differential neuroanatomical representations as compared with the universal language network that has been based on alphabetic languages. The research framework consisted of two levels: direct and converging evidence, through three lines of investigations. Study 1 and Study 2 provided direct evidence of the neural mechanisms for Chinese character processing. Study 1 set the stage for this research by summarizing the neural networks underlying Chinese orthographic, phonological, and semantic processing independently. A meta-analysis was conducted on existing fMRI studies that investigated the neural substrates underlying Chinese character processing. The results demonstrated the divergent activation for three language-processing components and consolidated the findings of additional recruitment of the left middle frontal gyrus and the right ventral occipito-temporal cortex for Chinese character processing as compared with the universal language network. The additional regions are thought to form a sub-network that might be specific to Chinese character processing. Regions-of-interest (ROIs) were defined based on the meta-analysis findings and a priori ROI approaches were implemented in the subsequent studies to examine the involvement and integrity of the sub-network. Study 2 directly examined the involvement of the sub-network in Chinese character identification and homophone judgment with the aims to elucidate the functional roles of the ventral occipito-temporal cortex and the middle frontal gyrus in orthographic (Study 2a) and phonological processing (Study 2b), respectively. The bilateral ventral occipito-temporal cortices are involved in character form recognition, with the amount of activation modulated by lexicality effect and demands of orthographic analysis. The middle frontal gyrus is suggested to be a domain-general region that coordinates information from different domains, and thus it might be associated with orthography-to-phonology transformation in reading Chinese. Study 3 provided indirect evidence for the involvement of the sub-network in Chinese character processing by investigating the integrity of the sub-network in terms of how it might be affected by individual characteristics such as age and handedness. Study 3a examined age effects on the sub-network during word retrieval. Consistent with previous studies on alphabetic language speakers, the results showed increased bilateral inferior frontal activation and reduced default mode network deactivation in the older adults during the language tasks, indicating age-related changes in the neural correlates underlying word retrieval to be universal. However, age-related changes in the sub-network were also revealed by the ROI analysis, which suggest language-specific vulnerability to aging. Study 3b explored language dominance within the inferior frontal gyrus and the sub-network with respect to handedness. Handedness was indicative of the lateralization of all selected regions, and the lateralization was correlated between regions. While the lateralization of the inferior frontal gyrus seemed to be universal across speakers of different languages, spatial heterogeneity in language dominance was observed in the sub-network especially in the left-handers. These investigations shed light on the understanding of the functional roles and the integrity of the specialized sub-network for Chinese character processing. Identifying the differential activation of Chinese character processing provided important implications for clinical applications, such as pre-surgical planning and establishing models for intervention in language disorders.